Epidemiology of porcine deltacoronavirus among Chinese pig populations in China: systematic review and meta-analysis - Sun, Junying; Zhang, Qin; Zhang, Chunhong; Liu, Zhicheng; Zhang, Jianfeng (Frontiers in Veterinary Science, 2023)
Porcine deltacoronavirus (PDCoV) is a newly emerging and important porcine enteropathogenic coronavirus, and it seriously threatens Chinese and the global swine industry. We conducted a systematic review and meta-analysis to access the prevalence of PDCoV infection in pig population from mainland China. Electronic databases were reviewed for PDCoV infection in pig population, and meta-analysis was performed to calculate the overall estimated prevalence using random-effect models. A total of 39 studies were included (including data from 31,015 pigs). The overall estimated prevalence of PDCoV infection in pigs in China was 12.2% (95% confidence interval (CI), 10.2%–14.2%). Meanwhile, the estimated prevalence of PDCoV infection in pigs from Central China was 24.5% (95%CI, 16.1%–32.9%), which was higher than those in other regions of China. During the period of 2014–2021, the estimated prevalence of PDCoV infection was the highest in 2015 with the prevalence of 20.5% (95%CI, 10.1%–31.0%), and the lowest was in 2021 with 4.8% (95%CI, 2.3%–7.3%). The prevalence of PDCoV infection in sows was 23.6% (95%CI, 15.8%–31.4%), which was higher than those in suckling piglets, nursery piglets, and finishing pigs. The prevalence of PDCoV infection was significantly associated with sampling region, sampling year, pig stage, and clinical signs (diarrhea). This study systematically evaluated the epidemiology of PDCoV infection in Chinese pig population. This information will provide us with a more comprehensive understanding of PDCoV infection and be beneficial for establishing new controlling strategies worldwide.